MOOD STATES ON WORKING MEMORY AND BRAIN HAEMODYNAMIC RESPONSE USING OPTICAL TOPOGRAPHY MODALITY - FENG , YING XING (2016)
Higher cognitive brain functions such as language, planning and problem solving require the working memory (WM). Studies have shown that negative mood states impair the WM functions, related to activations at the prefrontal cortex (PFC) region. Previous works which were conducted based on Japanese and German subjects have reported a significant correlation between negative mood states and reduced PFC activation during the verbal WM task, however no significant correlation was found during the visuospatial WMtask. Before proceeding to investigate whether spatial WM function is invulnerable to impairment by negative mood states, it is essential to reaffirm that the relationship between negative mood and PFC activity is in fact a general phenomenon irrespective to WM task paradigm and subjects' anthropology factors. The relationship between induced mood states and the PFC activation using verbal n-back task paradigm is investigated, among multiracial subjects in Malaysia.